UWAYSIY – THE EXEMPLARY OF PATIENCE AND FAITH - Abduvohidova Rukhshona Doniyorbek qizi (PEDAGOGS, 2025)
Annotation:This article will talk about the life and work path of one of the brightest manifestations of the world of literature, World otin Uwaisi, his contribution to the literary norm, lyricism and the world of poetry.